Virus infections of the European Eel in North Rhine Westphalian rivers - Linna Danne; Lisa Horn; Anita Feldhaus; Daniel Fey; Sebastian Emde; Heike Schütze; Mikolaj Adamek; John Hellmann (Journal of Fish Diseases, 2022)
Viral infections have been suggested to play a role in the decline of the panmictic population of the European eel ( Anguilla anguilla ). However, despite the importance of knowledge about pathogenic eel viruses, little is known about their spread in the wild European eel population and only a few eel pathogenic viruses have been described so far. In this study, we aimed to investigate the health status of the A. anguilla stock in North Rhine Westphalia (NRW) State of Germany. For this purpose, we examined tissue samples of 16 elvers, 100 yellow eels and 6 silver eels, sampled from the rivers Rhine, Lippe and Ems. Virus detection was performed via a combination of cell culture and PCR. Next to the detection of frequently encountered pathogenic eel viruses (anguillid herpesvirus 1 and eel virus European X (EVEX)), we isolated the eel picornavirus 1 (EPV‐1) from tissue of yellow eels and elvers and demonstrate the distribution of EPV‐1 in wild eel population in NRW.

Aalabwanderung an der Wasserkraftanlage Unkelmühle - zwei Methoden, ein Ergebnis? - Detlev Ingendahl; Lisa Heermann; Jost Borcherding; Sebastian Emde; Stefan Staas; Maxim Teichert (WASSERWIRTSCHAFT, 2021)